Knowledge and exposure to complementary and alternative medicine in paediatric doctors: a questionnaire survey - Goldstein Amanda; Kawai Grace; Fountain-Polley Simon; Ninan Titus (BMC, 2007)
Abstract Background Complementary and alternative medicines are increasingly used by the general population. A survey was conducted to ascertain the knowledge of Complementary and Alternative Medicines (CAMs) amongst paediatric physicians, and whether seniority increases the likelihood of its use being considered in consultations, or of families discussing it. Methods Anonymous survey of general paediatric doctors in a large inner-city district general hospital (DGH) and tertiary children's centre (TC) using a questionnaire. Statistical analysis was calculated using Minitab. Results 43/49 (88%) questionnaires were returned correctly. 13 (30%, CI 17 - 46%) doctors had personally used CAMs. 24 (56%, CI 40 - 71%) of their families had used CAMs. 13 (30%, CI 17 - 46%) had received formal CAMs education. 21 (49%, CI 40 - 71%) could name a total of 5 types of CAMs. Consultants were significantly more likely to ask about CAM use than middle-grades and juniors (p < 0.05, CI 48 - 93%, 35 - 90%, 8 - 33% respectively) and have had a clinical encounter where they felt it was significant. 32 (74%, CI 59 - 86%) of the clinicians had been asked about CAMs. 33 (77%, CI 61 - 88%) of doctors had successful CAM use reported to them, and 20 (47%, CI 31 - 62%) had failure of CAMs reported to them. Conclusion CAM use is relatively common in paediatric doctors and their families. They have received little formal CAMs education. Consultants were more likely than juniors to ask about CAM use and have had a clinical encounter where it played a significant part. Around half of all doctors irrespective of grade have been asked about CAMs in a clinical encounter.